Effect of study partner on the conduct of Alzheimer disease clinical trials - Grill, Joshua D. (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: Alzheimer disease (AD) dementia clinical trials require 2 participants: a patient and a study partner. We assessed the prevalence of study partner types and how these types associate with patient-related outcome measures. METHODS: Retrospective analyses of 6 Alzheimer’s Disease Cooperative Study (ADCS) randomized clinical trials were conducted. Study partners were categorized as spouse, adult child, or other. Prevalence of study partner type and associations between study partner type and trial outcomes including study completion and placebo decline on the Mini-Mental State Examination, the Alzheimer’s Disease Assessment Scale–cognitive subscale, the Clinical Dementia Rating scale Sum of the Boxes score, and the ADCS–Activities of Daily Living were examined. RESULTS: More participants (67%) enrolled with spouses than adult children (26%) or other study partners (7%). Participants with spouse partners had a lower dropout rate (25%) than those with adult child (32%) or other study partners (34%); only the difference vs others was statistically significant. Participants with adult child and other partners randomized to placebo performed worse at baseline than those with spouse partners on the ADCS–Activities of Daily Living (p = 0.04), but were not different at 18 months. There were no differences at baseline for the Mini-Mental State Examination, Clinical Dementia Rating scale Sum of the Boxes score, or Alzheimer’s Disease Assessment Scale–cognitive subscale. In multivariate models of the rates of change over time among placebo participants, no differences among study partner groups reached statistical significance. CONCLUSIONS: Patients with nonspouse caregivers less frequently participate in AD dementia trials. Increased enrollment of AD patients with nonspouse caregivers may require additional recruitment and retention strategies.